Antyk – germańskość: dwie tradycje nazizmu? - Grzeszczuk-Brendel, Hanna (Collectanea Philologica, 2024)
Nazi ideology appropriated many traditions of thought, syncretistically combining them to justify German’s racial superiority. This belief stems from Volkist thought, with its concept of the Aryan/Germanic superman, racial purity and the connection to ‘blood-and-earth’. Ancient art, which was the formal basis for the architecture and sculpture of the Third Reich, was also treated as an expression of Germanic culture. The article discusses how Nazi ideology attempted to combine the volkist concept of Germanicness with the legacy of ancient art, and use both to legitimise the idea of racial superiority justifying the practice of conquest, annihilation and subjugation of other peoples. The juxtaposition of classicist artistic concepts with the shaping of a “Germanicˮ nature also reveals the total dimension of the indoctrination of its own citizens to participate in the construction of a new “orderˮ.